Robin Williams cool Mac apps a guide to iLife '05, .Mac, and more! - Tollett, John (Peachpit Press, 2005)
Robin Williams Cool Mac Apps: A Guide to iLife 05, .Mac, and More is a companion volume to Robin Williams Mac OS X Book, Tiger Edition. Together they continue the tradition of Robin's classic guide to the Mac OS, The Little Mac Book . Because Apple now provides a long list of useful applications with Mac OS X, its state-of-the art operating system, it's impractical to cover all of the Mac OS in one volume. This book gives you detailed explanations and tutorials of the main applications that Mac OS X installs on your computer. In addition, you'll learn how subscribing to a .Mac account can enhance your digital lifestyle. John and Robin cover each application in detail in the clear and friendly style for which their award-winning books are known. Through tutorials, tips, and techniques you'll learn how to use each of the powerful apps--both individually and as part of an integrated, interactive suite. Whether you're a new or veteran user, you'll welcome this book's easy approach to all that's new (and not so new) in Tiger's application collection. You'll find an entire chapter on GarageBand 2, Apple's newly updated consumer-level music-making software. You'll also learn everything about getting on the Internet and using email, including the greatest Web browser, Safari; the way-cool iChat AV, which adds audio and video to instant messaging; iTunes, which includes access to the revolutionary Apple iTunes Music Store; iCal, Apple's sleek and shareable calendar application; Dashboard, the handy strip of desktop "widget" applications (including stock tickers, RSS feeds, address book, and more); iMovie, Apple's newly updated movie-making software with HD capabilities and advanced editing tools, and much more
Print version record
Keywords: Mac OS; Operating systems (Computers); Macintosh (Computer) -- Programming; Application software; Systèmes d'exploitation (Ordinateurs); Macintosh (Ordinateur); Programmation; Logiciels d'application; operating systems; Macintosh (Computer); Programming